2010
DOI: 10.1680/macr.2008.62.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Air-blast-loaded, high-strength concrete beams. Part I: Experimental investigation

Abstract: The structural behaviour of concrete beams subjected to air blast loading was investigated. Beams of both highstrength concrete (HSC) and normal-strength concrete (NSC) were subjected to air blasts from explosives in a shock tube and for reference were also loaded statically. Concrete with nominal compressive strengths of 40, 100, 140, 150 and 200 MPa were used and a few beams also contained steel fibres. Furthermore, beams with two concrete layers of different strength were tested. All beams subjected to stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…Previous studies reported that RC beams failed statically in the pure flexure mode may shift to the shear failure mode in impact tests (Magnusson et al, 2010a(Magnusson et al, , 2010bMicallef et al, 2014;Ozˇbolt and Sharma, 2011;Saatci and Vecchio, 2009). Hughes and Beeby (1982) pointed out that shear failure may occur in RC beams due to activation of higher modes of vibration under impact loads.…”
Section: Dynamic Response Of Rc Beams Under Impact Loadsmentioning
confidence: 95%
“…Previous studies reported that RC beams failed statically in the pure flexure mode may shift to the shear failure mode in impact tests (Magnusson et al, 2010a(Magnusson et al, , 2010bMicallef et al, 2014;Ozˇbolt and Sharma, 2011;Saatci and Vecchio, 2009). Hughes and Beeby (1982) pointed out that shear failure may occur in RC beams due to activation of higher modes of vibration under impact loads.…”
Section: Dynamic Response Of Rc Beams Under Impact Loadsmentioning
confidence: 95%
“…In the simulations, the air blast load was applied as a piece-wise linear approximation of a registered pressure-time curve obtained from the experiments (Magnusson et al, 2009). Ten data points were used to describe the amplitude of a pressure load on the surface, which thus varies linearly over time between data points, as shown in the example given in Figure 1.…”
Section: Air Blast Loadingmentioning
confidence: 99%
“…1 mm respectively. The distance from the bottom surface of the beam to the centre of the tensile rebars was 33 mm, which is the nominal measurement for the beams in the experiments (Magnusson et al, 2009). A modelled beam with five rebars of diameter 16 mm and with an interface layer around each rebar is illustrated in Figure 5.…”
Section: Beam Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the steel, the concrete material also has a significant contribution in determining the panel's performance. Previous studies concluded that HSC is too brittle to achieve its full strength potential [5,8]. The incorporation of fibre is a good way to overcome the brittleness of plain HSC.…”
Section: Introductionmentioning
confidence: 99%